Women's empowerment and nutrition status: The case of iron deficiency in India. (October 2019) - Gupta, Soumya; Pingali, Prabhu; Pinstrup-Andersen, Per
Highlights: Non-dietary pathways can potentially address micronutrient outcomes for women. Women's iron status improves with higher empowerment levels in agriculture. Women's minimum dietary diversity score is unable to reflect iron status. Detailed data on blood tests fills the gap for reliable iron estimates in India. Abstract: In this paper we study the relationship between women's empowerment in agriculture and their iron deficiency status in Maharashtra, India. This is the first time the Women's Empowerment in Agriculture Index (WEAI) has been used in association with explicit measurement of medical biomarkers for women's iron deficiency status. Using primary data for 960 women we find that the log odds of a poor iron status in women decline as women's empowerment levels in agriculture improve. Further, this decline is seen in the presence of multiple dietary diversity measures (dietary diversity score, share of rice and wheat in the diet, total iron intake and iron intake from iron-rich food groups – all for 24-h and 30-day recalls) suggesting that in addition to dietary pathways women's empowerment can play a role in addressing micronutrient deficiencies like those of iron in a vulnerable sub-group of the population. It also reinforces the need to move away from the 'staple grain fundamentalism' that has characterized agricultural policy in India, towards more nutrition-sensitive food systems.